Optimalisasi Produksi Alat Gali-Muat dan Alat Angkut pada Proses Pengupasan Overburden untuk Mencapai Target Produksi per Bulan pada Penambangan Batubara PT. Pengembangan Investasi Riau Coal Mine Project Desa Pematang Benteng Kecamatan Batang Peranap Kabupaten Indragiri Hulu Provinsi Riau - Agung Pujangga; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2021)
Based on field observation, The production of stripping overburden at PT. Pengembangan Investasi Riau on November 2020 didn’t reach target. It was caused by the high number of losstime that occur during the production process.Digging-Loading Equipment used for Stripping Overburden on one of fleet is 1 Unit 1 unit Excavator Kobelco SK480LC (EE01) with Hauling Equipment, 9 unit Dump Truck Quester CWE 370 (DT78, DT81, DT84, DT85, DT86, DT87, DT89, DT90 dan DT91). To determine potential of improvement from a production process and effectiveness of using equipment, then an analysis called Overall Equipment Effectiveness (OEE) was carried out. OEE value for actual Digging-Loading Hauling Equipment indicates a very low value (< 85%). Next, used the Fishbone Diagram to find cause and effect from high number of losstime that occurs on the Equipment. Finally, the loss time is repaired due to human factors with the smallest standard tolerance method. After analyzing and improving with these methods, the production of Stripping Overburden on the fleet theoretically increased ± 2000 bcm from the previous production. OEE value still shows a fairly low value (< 85%) from World Class OEE Standard (> 85%). In addition, operational cost for digging-loading dan hauling equipment also increase along with the increase in production.